(untitled) (Revista Educación Física Chile, 2022)
The objective was to describe the application of biomechanics in relation to football. For which documentary screening techniques used to collect information. Through which became known biological and mechanical characteristics and potential uses in football, both for diagnosis, to monitor qualitative and quantitative variables. Finally, through the review carried out considering that the biomechanical characteristics should be used by professionals working in football, as its principles could help to achieve better athletic performance, ie the physical, technical, tactical and physiological, respectively.